Pengaruh Kecerdasan Emosional, Perilaku Belajar, dan Kepercayaan Diri terhadap Tingkat Pemahaman Mahasiswa Akuntansi - Darniati A. Salogo; Suciawati H. Pate; Ikhlas Ul Aqmal (Journal of Accounting, Economics, and Business Education, 2026)
This study aims to analyze the influence of emotional intelligence, learning behavior, and self-confidence on the level of understanding of Accounting Students at Gorontalo State University, both partially and simultaneously. This study involved 104 Accounting students from the 2020 to 2024 intakes as participants, with data collected through a questionnaire using Google Forms. The research instrument used a Likert Scale to measure respondents' responses, while data analysis was conducted using Multiple Regression assisted by SPSS. The analysis techniques used included descriptive statistics, validity tests, reliability tests, classical assumptions, and partial and simultaneous hypothesis testing. The results showed that partially, emotional intelligence and learning behavior had a significant influence on accounting understanding, while self-confidence did not have a significant effect on accounting understanding. However, simultaneously, these three factors together had an influence on the understanding of accounting students at Gorontalo State University